Reporting on Studies Using Single-Subject Experimental Methods - Wolery, Mark; Dunlap, Glen (Journal of early intervention, 2001)
This paper describes guidelines for reporting findings from studies using single subject methods, an approach from which early intervention has benefited substantially. Guidelines address: the foundations of the study, what was done to whom under what situations, what the data say, and what the findings mean. (Contains references.) (DB)